THE POSSIBILITIES OF USING EDUCATIONAL POTENTIAL OF THE INTERNET ENVIRONMENT FOR THE PREVENTION OF DEVIANT BEHAVIOR OF YOUTH - Olga Lugovaya; Antonina Polikarpova; Irina Chernikova (Вестник Северо-Кавказского федерального университета, 2022)
The article provides an analysis of the socializing opportunities of the Internet environment for the younger generation. The positive and negative impact of the Internet on the personal development and socialization of young people is considered. Features ofmanifestation of deviant behavior in cyberspace are presented. The authors propose a model for the prevention of deviant behavior in cyberspace, identified the conditions for improving the efficiency of the Internet as an agent ofpositive socialization of young people.